Ameliorated photodegradation performance of polyethylene and polystyrene films incorporated with ZnO-PVP catalyst - Lam, S.-M. (Elsevier Ltd, 2022)
Ubiquitous occurrence and indiscriminate disposal of plastic waste have urged us to search a new and useful strategy to battle the menace of plastic contamination. Herein, we demonstrated an effective way to degrade two common plastic films, namely polyethylene (PE) and polystyrene (PS) through ZnO-modified by polyvinylpyrrolidone (ZnO-PVP) under direct sunlight. Incorporation of PVP can effectively reduce the particle size and prolong the optical response range in the solar spectrum of the developed ZnO samples. As compared to unmodified ZnO and virgin films, ZnO-PVP catalysts exhibited prominent solid phase photodegradation of PE and PS. High surface area of ZnO-PVP can improve the interaction with plastic film texture and thereby resulted in the boosted charge mobility for the photodegradation of polymeric substances. The surface textures of polymer films were efficiently deteriorated over ZnO-PVP under sunlight irradiation. These findings were corroborated with the production of carbonyl, peroxides and vinyl unsaturated groups as monitored by infrared spectrometer. The mechanical strength and thermal stability of the composite films also restrained upon sunlight exposure. The holes and hydroxyl radicals as core species were produced by ZnO-PVP during the course of plastic photodegradation. Based on these analyses, a conceivable mechanism was postulated and was in well accordance with the obtained data. Â© 2022 Elsevier Ltd